PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PERUSAHAAN - Dida Adi Setyadharma; Indira Januarti (Diponegoro Journal of Accounting, 2019)
This study aims to examine the impact of working capital to profitability. Working capital is proxied by Days of sales Outstanding (DSO), Days of Inventory Outstanding (DIO), and Days of Payable Outstanding (DPO).The population in this study consists of all listed firms in Indonesia Stock Exchange in year 2012-2014. Sampling method that is used in this study is purposive sampling. Total sample that is used in this research is 87 companies. The statistical method used in this study is multiple linear regression analysis. The results of this study indicate that DSQ, DIO and DPO affect significantly to Profitability (Return on Assets). Those variables (DSQ, DIO and DPO) together influence the dependency—simultaneously, beside that each variable except DSO individually also influence the dependency—partially.